How much does a boat cost after you buy it? Q & A with Boat Buying Expert Gary Fretz - Jessica and Ryan Adventures (2017)
This week we try something new and interview Gary Fretz. With nearly 30 years of experience buying and selling boats Gary knows a thing or 3 about the industry and agreed to help us by answering some of the most common questions you guys ask us. Gary's email: bigyachts@gmail.com Gary's Website: http://bit.ly/garyfretz Support us on Patreon?!: http://bit.ly/jandr-patreon Get a t-shirt(or 3!): http://bit.ly/HonuBrandTeeSpring Free floorplan tool: http://bit.ly/floorplantool Our Instagram: @jessicaandryanadventures Arya's Instagram: @arya.samoyed Our facebook page: https://www.facebook.com/jessicaandry... Feel free to send us any questions to: jessicaandryanadventures@gmail.com